Actin is associated with tissue injury in trauma patients and produces a hypercoagulable profile in vitro. Issue 1 (July 2020) - Coleman, Julia R.; Moore, Ernest E.; Freeman, Kalev; Grubinger, Nicholas D.; Hennig, Grant W.; Cohen, Mitchell J.; Samuels, Jason M.; Hansen, Kirk
Abstract : BACKGROUND: While tissue injury provokes fibrinolysis shutdown in trauma, the mechanism remains elusive. Cellular death causes release of structural proteins, including actin and myosin, which may interact with clot formation and structure. We hypothesized that tissue injury is associated with high circulating actin and that actin produces a hypercoagulable profile with decreased fibrinolysis in vitro. METHODS: Blood was collected from trauma activation patients at a single Level I trauma center for thrombelastography and proteomics. Proteomic analyses were performed through targeted liquid chromatography coupled with mass spectrometry using isotope-labeled standards for quantification of actin and its endogenous inhibitor gelsolin. Based on the results, we added physiologic concentrations of cytoskeletal G-actin to whole blood from healthy volunteers and analyzed changes in thrombelastography, as well as to plasma and examined clot architecture using confocal microscopy of fluorescently labeled fibrinogen. RESULTS: Overall, 108 trauma patients were included: majority (71%) men, median age of 32.7 years, 66% blunt mechanism, median New Injury Severity Score (NISS) of 41. Compared with patients without severe tissue injury (NISS < 15, n = 10), patients with severe tissue injury (NISS > 15, n = 98) had higher levels of circulating actin (0.0428 vs. 0.0301, p = 0.02). Further, there was a trend toward lower gelsolin levels in patients with fibrinolysis shutdown (0.1844 vs. 0.2052, p = 0.17) and tissue plasminogen activator resistance (0.1676 vs. 0.2188, p = 0.06). Ten healthy volunteers were included in the in vitro experiments (50% male; median age, 31.3 years). Actin significantly increased angle (40.0° to 52.9°, p = 0.002) and decreased fibrinolysis (percent clot lysis 30 minutes after reaching maximum amplitude, 4.0% to 1.6%; p = 0.002), provoking fibrinolytic shutdown in three patients. The addition of actin to control plasma decreased fiber resolvability of fibrin clots, monitored by microscopy, and decreased plasmin-mediated fibrinolysis. CONCLUSION: Actin increases clot propagation and provokes fibrinolysis shutdown in vitro, through a mechanism of plasmin inhibition. High circulating levels of actin are present in trauma patients with severe tissue injury, suggesting actin contributes to fibrinolysis shutdown in the setting of tissue injury. Abstract : Supplemental digital content is available in the text.